Spinal muscular atrophy with respiratory distress type 1 (SMARD1): a rare cause of hypotonia, diaphragmatic weakness, and respiratory failure in infants - Pekuz, Serdar; Güzin, Yiğithan; Sarıtaş, Serdar; Kırbıyık, Özgür; Ünalp, Aycan; Yılmaz, Ünsal (The Turkish Journal of Pediatrics, 2022)
Background. Spinal muscular atrophy with respiratory distress type 1 (SMARD1) is a very rare autosomal recessive disorder caused by mutations in the immunoglobulin μ-binding protein-2 (IGHMBP2) gene on chromosome 11q13.2-q13.4. The initial symptoms of patients with SMARD1 are respiratory distress and distal muscle weakness manifesting in the infantile period due to progressive degeneration of α-motor neurons. Preterm birth, intrauterine growth retardation, feet deformities, sensory and autonomic neuropathy are other main features. Case. Herein, we report the characteristics of a 6-year-old Turkish girl with a diagnosis of SMARD1 confirmed by homozygous c.1738G > A (p.Val580Ile) missense IGHMBP2 variant. She had unusual features such as vocal cord paralysis, nystagmus, and lack of congenital foot deformities besides typical findings including hypotonia, respiratory distress, and diaphragmatic weakness in the early infantile period. Epileptic seizures, cognitive impairment, and brain magnetic resonance imaging (MRI) abnormalities were other, unexpected, features which developed during the course of the disorder possibly due to several hypoxic episodes. Conclusions. SMARD1 should be kept in mind in hypotonic infants with diaphragmatic weakness and respiratory failure during the early infantile period, even in the presence of unexpected findings including vocal cord paralysis, nystagmus, epileptic seizures, and brain MRI abnormalities.